A new avirulence gene of Leptosphaeria maculans, AvrLm14, identifies a resistance source in American broccoli (Brassica oleracea) genotypes. (31st August 2021) - Degrave, Alexandre; Wagner, Marine; George, Pierre; Coudard, Laurent; Pinochet, Xavier; Ermel, Magali; Gay, Elise J.; Fudal, Isabelle; Moreno‐Rico, Onesimo; Rouxel, Thierry; Balesdent, Marie‐Hélène
Abstract: In many cultivated crops, sources of resistance to diseases are sparse and rely on introgression from wild relatives. Agricultural crops often are allopolyploids resulting from interspecific crosses between related species, which are sources of diversity for resistance genes. This is the case for Brassica napus (oilseed rape, canola), an interspecific hybrid between Brassica rapa (turnip) and Brassica oleracea (cabbage). B. napus has a narrow genetic basis and few effective resistance genes against stem canker (blackleg) disease, caused by the fungus Leptosphaeria maculans, are currently available. B. rapa diversity has proven to be a valuable source of resistance ( Rlm, LepR ) genes, while B. oleracea genotypes were mostly considered susceptible. Here we identified a new resistance source in B. oleracea genotypes from America, potentially effective against French L. maculans isolates under both controlled and field conditions. Genetic analysis of fungal avirulence and subsequent cloning and validation identified a new avirulence gene termed AvrLm14 and suggested a typical gene‐for‐gene interaction between AvrLm14 and the postulated Rlm14 gene. AvrLm14 shares all the usual characteristics of L. maculans avirulence genes: it is hosted in a genomic region enriched in transposable elements and heterochromatin marks H3K9me3, its expression is repressed during vegetative growth but shows a strong overexpression 5–9 days following cotyledon infection, and it encodes a small secreted protein enriched in cysteine residues with few matches in databases. Similar to the previously cloned AvrLm10‐A, AvrLm14 contributes to reduce lesion size on susceptible cotyledons, pointing to a complex interplay between effectors promoting or reducing lesion development. Abstract : Cloning of avirulence gene AvrLm14 in Leptosphaeria maculans allowed us to identify the first resistance gene to the fungus in Brassica oleracea ; therefore B. oleracea diversity may be exploited to find novel resistance to the disease.